All optical design of binary adders using semiconductor optical amplifier assisted Mach–Zehnder interferometer. Issue 9 (September 2015) - Datta, Kamalika; Chattopadhyay, Tanay; Sengupta, Indranil
Abstract With the progress in research in the field of optical computing, architectural designs of various digital components and systems using all-optical technology are being explored. Implementations of basic gates like AND, OR, XOR, etc. and arithmetic components like adder, subtracter, etc. have already been investigated in the all-optical domain. Among the various alternatives, interferometric devices have shown great promise due to their high-speed photonic activity and ease of manufacturing. Many of these works consider semiconductor optical amplifier (SOA) assisted Mach–Zehnder Interferometer (MZI) for the implementation. In this paper we present all-optical implementations of binary adders using MZI switches, which have been validated through numerical simulation of the switch models. Some performance parameters of the design have also been evaluated. Three designs have been explored – a ripple-carry adder, an extension with faster carry propagation, and a carry save adder. The design complexities have been compared with some recently published works, both in terms of optical cost and delay.